Influência de cultivares de batata-doce resistentes e suscetíveis a Euscepes postfasciatus fairmaire (Coleoptera: Curculionidae) sobre o parasitismo, sobrevivência e a biologia de Catolaccus grandis burks (Hymenoptera: Pteromalidae) - Wanderley, Paulo A. (2003)
The influence of four resistant and two susceptible genotypes of sweet potato to Euscepes postfasciatus Fairmaire on parasitism and biology of Catolaccus grandis Burks were evaluated under laboratory conditions. Six sweet potato roots of each genotype were infested with E. postfasciatus adults during 40 days. After this period the larvae were taken, weighted and encapsulated in parafilm. Five larvae were offered in free choice and no choice tests to C. grandis pregnant females for 12h. Five replications were used. The parasitized larvae and the eggs of the parasitoid were counted. Three daily observations were made to determine the developmental time of phases and parasitoid survival. C. grandis females can distinguish E. postfasciatus larvae reared on susceptible and resistant roots, prefering to parasitize larvae reared on susceptible roots. C. grandis survival was higher when the parasitoid was reared on larvae originated from susceptible roots and the number of emerged females was higher on larvae reared on hosts originated from susceptible roots.